A numerical study on utilizing horizontal flat-panel ground heat exchangers in ground-coupled heat pumps. (March 2020) - Habibi, Mohammad; Amadeh, Ali; Hakkaki-Fard, Ali
Abstract: Horizontal ground heat exchangers (GHEs) have a lower cost in comparison to vertical ones; however, they require more land area. For the sake of reducing the required land area for horizontal GHEs, flat-panel GHEs have been recently introduced. In this piece of research, a 3-D numerical model has been developed to predict the thermal performance of flat-panel GHEs. In this study, at first, the thermal performance of a flat-panel GHE has been compared with that of linear horizontal ones. The results demonstrate that the flat-panel GHE has a better thermal performance of about 27% in comparison to an arrangement of linear GHEs with a value of 0.5 m for pipe spacing. In the second part of this study, the effects of three different parameters including soil thermal conductivity, buried depth, and the width of the flat-panel GHE on the thermal performance of the GHE have been investigated. The obtained results show that even though increasing buried depth enhances the thermal performance, the rate of enhancement decreases at the same time. Furthermore, it is established that increasing width is not of great significance when the GHE is more than 10 m wide. Highlights: The thermal performance of a typical flat-panel GHE is numerically investigated. The model considers variations in the cooling load and the ground surface temperature. The thermal performance of linear GHEs is compared with that of flat-panel GHEs. The effects of three parameters on the performance of flat-panel GHEs are examined.